Antioxidant, Analgesic, Antimicrobial and Molecular Docking Studies of the Leaves of Oroxylum indicum (L.) Kurz. (Dhaka University Journal of Pharmaceutical Sciences, 2022)
This study presents the findings of in vivo, in vitro and in silico investigations of the Oroxylum indicum (L.) Kurz leaf extracts. Various fractions namely chloroform (CF), ethyl acetate (EAF), n-hexane (HF) and aqueous fractions (AF) obtained from the crude extract were subjected to biological investigations. In DPPH based free radical scavenging assay, CF and MF fractions showed potent antioxidant activity with IC50 9.70 g/ml and 10.46 g/ml as compared to IC50 8.56g/ml for the standard ascorbic acid. The CF and HF fractions of O. indicum (L.) Kurz leaves exhibited mild antimicrobial activity. In analgesic activity screening by acetic acid induced writhing method, EAF showed significant writhing inhibition of 68% and 72%, at doses 150 mg/kg and 300 mg/kg, respectively. In tail immersion method, EAF also showed potent analgesic activity with reaction time of 1.816 ± 0.047 and 2.15 ± 0.041 min, after 30 minutes following oral doses of 150 mg/kg and 300 mg/kg, respectively. Molecular docking of previously isolated compounds from O. indicum (L.) Kurz leaf extracts were docked against cyclooxygenase-1 (COX-1) and cyclooxygenase -2 (COX-2) and revealed that the flavonoids baicalein and chrysin may be responsible for the analgesic activity. Lipinski’s rule of five was also calculated for the compounds to assess drug likeliness.Dhaka Univ. J. Pharm. Sci. 21(1): 85-94, 2022 (June)